PEMBERITAAN KASUS KORUPSI TIMAH 271 T PADA LAMAN KOMPAS.COM: STUDI WACANA BERBANTUAN KORPUS - Budi Utami, Dewi Tri; Sidiq Budiawan , Raden Yusuf; Nayla, Azzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The news of the 271 T tin corruption case was widely reported in online mass media. This study aims to analyze the news coverage of the 271 trillion tin corruption case on Kompas.com using Theo Van Leeuwen's discourse analysis model. The results showed that there were three social actors represented, namely the perpetrator (Harvey Moeis) with a focus on his role as the main suspect, a third party (the Attorney General's Office) who stood out in the law enforcement process, and the victim (the state) who was highlighted through the amount of financial losses. In addition, analysis of the representation of social action reveals three actions: corruption positioned as a major crime with a wide impact, law as an instrument of justice, and losses emphasized through the mention of large numbers and their impact on the economy and the environment. This research concludes that Kompas.com's reporting frames the tin corruption case as a multidimensional crime that harms various aspects of people's lives, while emphasizing the importance of law enforcement to restore public trust.